Nurses’ Pain Management Challenges - Rojaye, Justin Oluwasegun (Nursing and Health Sciences Journal (NHSJ), 2024)
Pain is the most common medical issue that older people face in a long-term care facility. Nurses have a critical role in helping residents manage their pain. This research looked at nurses' pain management challenges in long-term care facilities. The site for this research was a chosen long-term care facility in Ontario, Canada, a 160-bed nursing home for the elderly that provides various nursing and medical care services. Semi-structured focus group interviews lasting about an hour were done. This study's population consisted of 45 nurses. The researcher chose a sample of 25 nurses using a purposive sampling strategy. The data was reviewed using qualitative data analysis to detect recurring concerns. This research revealed the necessity of identifying and overcoming obstacles to effective pain management and reinforcing good practices in long-term care homes; better pain management practices are necessary to manage pain in a long-term care home. This study demonstrated the importance of recognizing and overcoming barriers to the effective management of pain and reinforcing good practices in long-term care homes. Therefore, improved pain management practices are required to manage pain in a long-term care home effectively. The overall benefits of pain management practices in long-term care homes expand nurses' clinical knowledge in the care of residents living in nursing homes